Antimicrobial activity of comfort related properties of silk treated with herbal extracts in making of reusable masks (Bioscience Journal, 2023)
The study was aimed at divulging an eco-friendly antimicrobial finish on 100 % silk woven fabric. The leaves’ extract of Azadirachata indica, Butea monosperma and Litche chinensis were used as the development of eco-friendly antimicrobial finish. The antimicrobial property and comfort related property were checked before and after applying antimicrobial finish. In comfort related property absorbency & air permeability were checked. The ASTEM E2149 Shake Flask method was used to check antimicrobial finish and AATCC method was used for checking fabric property. One way ANOVA statistical test was applied for analysis of results. The FTIR and SEM results showed the presences of finish on fabrics. In comfort related property, absorbency and air permeability was increased. The results showed that antimicrobial finish made 100% reduction against microorganism up to 25 washes which can be used in making reusable masks fight against COVID- 19.